Performance evaluation of ProJet multi-material jetting 3D printer. Issue 1 (2nd January 2017) - Yang, Hongyi; Lim, Jingying Charlotte; Liu, Yuchan; Qi, Xiaoying; Yap, Yee Ling; Dikshit, Vishwesh; Yeong, Wai Yee; Wei, Jun
ABSTRACT: The purpose of this paper is to quantitatively evaluate the performance of a multi-material jetting 3D printer, ProJet 5500X, especially the capability for micro manufacturing. Unlike other single material 3D printer, ProJet 5500X uses photopolymers as the build material and wax as the support material. The building performance was evaluated by building a modified version of the standard benchmark model with a high-resolution printing mode. The dimensional error, forming quality and surface roughness of the printed parts have been measured and analysed using a microscope, a 3D coordinate measuring machine and a surface profilometer. Using wax as the support material, fine features as small as 0.25 mm, lateral features and sharper edges could all be properly built, despite the rough side surfaces observed in the printed part. Identical features (3 mm pins) were precisely built with an accuracy of 15 µm. The research provides first-hand detailed performance knowledge in the ProJet system for understanding the working principle and comparison with other 3D printing systems.